Musculoskeletal simulation of professional ski jumpers during take-off considering aerodynamic forces - Huang, Yi; Jiang, Liang; Chen, Xue; Sun, Qing; Zhang, Xiao; Tan, Xunan; Du, Yan; Zhang, Fangtong; Wang, Nannan; Su, Rufeng; Qu, Feng; Zhang, Guoqing; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Musculoskeletal simulation has been widely used to analyze athletes’ movements in various competitive sports, but never in ski jumping. Aerodynamic forces during take-off have been difficult to account for in dynamic simulation. The purpose of this study was to establish an efficient approach of musculoskeletal simulation of ski jumping take-off considering aerodynamic forces and to analyze the muscle function and activity. Camera-based marker-less motion capture was implemented to measure the take-off kinematics of eight professional jumpers. A suitable full-body musculoskeletal model was constructed for the simulation. A method based on inverse dynamics iteration was developed and validated to estimate the take-off ground reaction force. The aerodynamic forces, which were calculated based on the body kinematics and computational fluid dynamics simulations, were exerted on the musculoskeletal model as external forces. The activation and joint torque contributions of lower extremity muscles were calculated through static optimization. The estimated take-off ground reaction forces show similar trend with the results from past studies. Although inconsistencies between the simulated muscle activation and EMG from previous studies were observed in general, it is worth noting that the activation of the tibialis anterior, gluteus maximus, and long head of the biceps femoris was similar to specific EMG results. Among lower extremity extensors, soleus, vastus lateralis, biceps femoris long head, gluteus maximus, and semimembranosus showed high levels of activation and joint extension torque contribution. Results of this simulation can help to guide the physical training of jumpers for better take-off performance.